(untitled) (Revista Cientifica Ingenio Magno, 2022)
Abstract— Today the world is in constant motion, which is why it is essential to work with the best methods of transferring products that companies commonly distribute as goods and services, analyzing the situation, an agreement is established with an oncological IPS for the development of a general objective that gives as a solution a routing system that will send your articles in the shortest possible time; Mainly, the diagnosis carried out is available to evaluate those routing models that adapt to the parameters where the “TSP Methodology “ was established as ideal, consequently a database is used to make the route with the greatest benefit to it, restrictions are attributed as a maximum distance of travel per day in addition to a maximum of daily deliveries, Therefore the program is subjected to changes that modify the shipping times to adapt and be an optimal system for this, the average times between a delivery point and another for the different locations where shipments are made, finally a cost study would be presented to affirm or deny whether this transport system is adequate for the company when working with its own vehicle.